Mental workload and its effects on work-life balance – a case study - Nyberg, Rita (My University, 2013)
The economic downturn, competitive pressures, downsizing and reorganizations have created pressures for firms to identify possibilities to reach greater surplus and many employees are asked to do more with less. In these times, it is possible that employees experience increasingly heavy mental workload, even though it is not related to only this time period but to characteristics of the work, individual and work environment as well. This study discusses how individuals experience the effects of mental workload on their work-life balance. The study was conducted by using the interpretative phenomenological analysis (IPA) method. The study is a single case study and it was conducted in Finnish and Swedish HR departments of a large multinational corporation. The theoretical framework of the study is created round the concepts of mental workload and work-life balance. Mental workload is often linked to the feelings of stress and strain, and in a longer period of time even feelings of job exhaustion may appear. In these situations, in other words when the mental workload becomes heavier, it seems that the feeling of fatigue becomes increasingly present. The study indicates that the heavy mental workload has a negative influence on individual’s feeling of work-life balance. Individuals, who experience heavy mental workload seem to have feelings of tiredness, exhaustion and even fatigue. However, majority of the interviewees experienced such mental workload that it does not have any major influence on their sense of work-life balance. Therefore, even though the consequences of experienced heavy mental workload may be very serious in a longer period of time, most of the employees seem to be able to manage their workload efficiently and know how to recover from work, and thus the effects on their work-life balance seem to be rather small.
Keywords: Mental workload; Work-life balance; Case study; fi=Johtaminen ja organisaatiot|en=Management and Organization|; fi=Master's Degree Programme in International Business|